ChatGPT perceptions, experiences, and uses with emphasis on academia - Ali, Haneen; Ali, Duha; Fatemi, Yasin; Bharadwaj, Suhas Sudhir (Frontiers in Education, 2025)
IntroductionWith artificial intelligence technologies such as ChatGPT becoming increasingly integrated into educational environments, understanding their influence on academic stakeholders is essential. This study investigates how exposure to ChatGPT and demographic factors shape perceptions of this emerging AI tool in higher education.MethodsA cross-sectional survey was conducted at Auburn University, involving 761 participants including both faculty and students. The survey examined technology exposure, ChatGPT familiarity, demographic variables (e.g., gender), and overall perceptions of ChatGPT in academic contexts.ResultsThe analysis revealed significant differences in exposure and attitudes toward ChatGPT, with gender emerging as a key variable. Males reported greater exposure and more favorable perceptions of ChatGPT compared to other groups. Familiarity with AI tools was positively correlated with supportive attitudes toward their use in education.DiscussionThese findings highlight the importance of AI exposure in fostering acceptance and effective utilization of tools like ChatGPT. The results suggest a need for inclusive and equitable strategies to integrate AI in academic settings, particularly for underrepresented or less-exposed groups. Further research is encouraged to guide ethical and effective AI adoption in education.